PENERAPAN TEKNOLOGI PENDINGIN SAPI PERAH DENGAN SPRINKLER DAN PENAMBAHAN DAUN KATUK (Sauropus androgyrus) KEDALAM UREA MULTI NUTRIENT MOLASSES BLOCK (UMMB) DI KOPERASI PETERNAKAN SAPI PERAH MANASSA DESA CENDANA KECAMATAN CENDANA KABUPATEN ENREKANG - Effendi Abustam; Muhammad Yusuf; Muhammad Zain Mide; Hikma M. Ali (State Islamic University (UIN) Alauddin, 2015)
ABSTRACT. Implementation of IbM through cooling technology for dairy housing, using sprinklers, and the addition of katuk leaves into UMMB in Manassa dairy farm cooperation were intended to improve the productivity of dairy cows as well as indirectly would increase the income of cooperativemembers. This program were involved training, theory and practice for making UMMB, installation of cooling technology for dairy housing, several aspects of dairy cattle reproduction, and quality testing for milk and dangke. This program was conducted during a period of six months (JulyDecember 2012). The results of this program showed that the participants could receive the given technology enthusiastically, followed by post-training application of these technologies. Application of technology for making UMMB in which added by 2% of katuk leaf powder in formulation resulted an IbM product of UMMB-katuk with high in nutrients. Similarly, the application of cooling technology for dairy housing resulted an IbM product of cooling housing technology that can improve milk production and quality of Manassa cooperative members. Interaction between technology of UMMB katuk and cooling technology resulted milk production and quality of milk as well as dangke were much better than without the application of these two technologies.